Cardio-respiratory reference data in 4631 healthy men and women 20-90 years: the HUNT 3 fitness study. - Henrik Loe; Sigurd Steinshamn; Ulrik Wisløff (PLoS ONE, 2014)
Purpose To provide a large reference material on key cardio-respiratory variables in a healthy population of Norwegian men and women aged 20-90 years. Methods Sub maximal and peak levels of cardio-respiratory variables were measured using cardiopulmonary exercise testing during treadmill running. Results The highest peak ventilation among men (141.9±24.5 L·min-1) and women (92.0±16.5 L·min-1) was observed in the youngest age group (20-29 years, sex differences p<0.001) with an average 7% reduction per decade. The highest tidal volumes were observed in the 30-39 and 40-49 year age groups among men (2.94±0.46 L) and women (2.06±0.32 L) (sex differences p<0.001), with a subsequent average 6% reduction per decade. Ventilatory threshold and respiratory compensation point were observed at approximately 77% and 87% of peak oxygen uptake (VO2peak) among men and women, respectively. The best ventilatory efficiency (EqVCO2Than) was observed in the youngest age group (20-29 years) in both men (26.2±2.8) and woman (27.5±2.7) (sex differences p<0.001) with an average 3% deterioration in ventilatory efficiency per decade. Conclusion This is the largest European reference material of cardio-respiratory variables in healthy men and women aged 20-90 years, establishing normal values for, and associations between key cardio-respiratory parameters. This will be useful in clinical decision making when evaluating cardiopulmonary health in similar populations.